Heart rate variability at rest and exercise: influence of age, gender, and physical training - Gregoire, J.; Tuck, S.; Yamamoto, Y.; Hughson, R. L. (Canadian Journal of Applied Physiology, 1996)
The adaptive responses of the cardiovascular system to regular physical activity appear to include a reduction in sympathetic (SNS) activity and an increase in parasympathetic (PNS) activity during rest and at different absolute intensities of exercise. In a cross-sectional design, trained individuals who exercised at least 5 days/week for 45 min/day or more were compared with age- and gender-matched untrained controls. There was a relative bradycardia in the trained groups at rest and at the same absolute intensity of exercise in both young and middle-aged subjects. There were no differences in indicators of PNS and SNS activity at rest in young subjects. There was a reduced SNS activity and increased PNS activity in middle-aged trained subjects versus their age-matched controls. Spectral analysis was capable of showing changes in autonomic control of heart rate at rest and across intensities of exercise. These data showed significant shifts to increased PNS and reduced SNS indicators at rest in trained versus untrained middle-aged subjects and in females in both age groups versus males.